Target Based Computational Drug Repositioning for Astrocytoma - Manzoor, Maria; Aslam, Irum; Azam, Shumaila; Khan, Zanib (International Current Pharmaceutical Journal, 2016)
Drug reposition is innovative method as it provides new ways to measure drug kinetics, multiplexed assays and others. In drug repositioning already approved drugs are used due to which time is not wasted on initial clinical trials. Market attainment cost for repositioned drugs is far less than the market attainment cost for new drugs. The secondary indications of most of the approved drugs and the availability of approved drug databases can provide an efficient way of searching safer drugs for new indications. Drug repositioning can provide an alternative method to explore the safe anti-cancer agents. Astrocytoma is the one type of Brain tumor. There are four types of Astrocytoma which arise in different part of the brain. The type IV that is Glioblastoma is very aggressive form of it. Many genes are involved in spreading of this disease but it is normally caused by Tp53. Mutations in the Tp53 gene are identified in about 28% of de novo GBM and 65% of secondary , thus indicating that Tp53 abnormalities are common in the progression of disease. The structure for Tp53 protein was obtained from RCSB PDB: RCSB Protein Data Bank. For repositioning Drugs are randomly selected from Drug Bank. Those drugs which have fewer side effects as compared to the drugs for Glioblastoma are selected as a candidate compounds for docking. Patch Dock server was used to perform molecular docking. Then among all selected drugs, some drugs are reposition on the basis of significant binding interactions with target protein TP53. Manzoor et al., International Current Pharmaceutical Journal, July 2016, 5(8): 63-68 http://www.icpjonline.com/documents/Vol5Issue8/01.pdf